(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
It is known that after the independence of Uzbekistan, a lot of attention was paid to education, especially general secondary education. In particular, in order to improve the quality of secondary education, large-scale schools have been built for many conveniences, and music and art schools for gifted students. The article discusses how well the designed schools have been built over the years.